Knowledge regarding Human Milk Banking and its Acceptability among Mothers at Bharatpur Hospital, Chitwan, Nepal - Sapkota, Devi Kumari; Thapa, Asha; Khanal, Durga (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Human milk banking is a system that collects, processes, stores and donated breast milk to infants who are unable to receive breast milk from their biological distributes mothers. It promotes optimal nutrition and health for vulnerable infants, particularly those who are premature, ill or have special medical conditions. This study aimed to assess the knowledge regarding human milk banking and its acceptability among mothers at Bharatpur Hospital, Chitwan, Nepal. Method: A hospital based descriptive cross-sectional study carried out among 135 mothers admitted at postnatal ward of the hospital. Data collected from June 15 to July 15, 2023 by using structured interview questionnaires. All collected data entered and analyzed using statistical package for social sciences (SPSS) to assess the knowledge regarding human milk banking and its acceptability among mothers. Result: The finding revealed that the mean age of respondents was 26.27(±4.92) year. Nearly half of respondents (49.6%) had average knowledge, 43% had poor knowledge, and only 7.4% had adequate knowledge regarding human milk banking. Likewise, most of (70.4%) the respondents expressed their acceptability toward human milk banking. There was significant association between ethnicity and level of knowledge. The level of knowledge was strongly correlation (r=0.846, p=<0.001) with acceptability regarding human milk banking. Conclusion: The study concluded that near about half of the respondents had average knowledge and few had adequate knowledge regarding human milk banking, though had more acceptability towards human milk banking. The finding suggests that to increase the knowledge on human milk banking to the mothers seen important to the public through health education.